Composition, distribution, and diversity of benthic Macroinvertebrate from Creeks around Lagos Lagoon, Nigeria - A.P. Onyena (Journal of Applied Sciences and Environmental Management, 2019)
Anthropogenic activities comprise a significant threat to ecosystem balance and biodiversity integrity. The most impacted groups of animals are macrobenthic fauna that live on, or bury within sediments. This study investigated the population of macrobenthic species from Abule Agege (Station A), Abule Eledu (Station B), and Ogbe (Station C) creeks adjoining Lagos Lagoon, Nigeria. The sediments containing the benthos were collected using a Van Veen grab between 0800 and 1100 hrs from June to November, 2016. Results showed a total of 374 organisms belonging to 13 genera, 13 families, 11 orders, 6 classes and 4 phyla. The phyla included Mollusca (238 species), Arthropoda (98 species), Annelida (36 species) and Chordata (2 species). Station A had 74 species, with the highest number (23 species) being recorded in the August and lowest number (3 species) in November. Station B had 220 species with 73 species sampled in September and 7 species in June. Station C had 80 species, with 25 species in June and the lowest in September (4 species). The Mollusc Tympanotonus fuscatus was the most dominant specie (40%), followed by Pachymelania aurita (21%) and Clibanarius africanus (16%). The abundance of Chironomous sp at Ogbe creek presents a high contaminated creek. There was high richness index in the study months. This can be attributed to the kind of human stressors that occurred at the differnt sites. The macrobenthic community structure analysis of the species recorded low diversity and abundance in the study stations,which depicts an environmentally stressed ecosystem.